Family Thriving During COVID-19 and the Benefits for Children’s Well-Being - Partington, Lindsey C.; Mashash, Meital; Hastings, Paul D. (Frontiers in Psychology, 2022)
Although the COVID-19 pandemic has raised deserved concern regarding adverse impacts on parents’ and children’s mental health, regulations like “sheltering-in-place” may have afforded parents novel opportunities to foster positive family connections, thereby bolstering well-being. Using latent profile analysis (LPA), we (a) distinguished family thriving during shelter-in-place (May-June 2020) from other patterns of family functioning, (b) tested potential predictors of family functioning profiles, and (c) examined if family thriving predicted subsequent child adjustment (September–October 2020). 449 parents in two-parent U.S. families with children aged 2–18 years completed online surveys assessing (a) parent–child relationship quality, parents’ positive psychological adjustment, children’s emotional well-being, and parenting efficacy and satisfaction as family functioning indicators, (b) financial, marital, parental psychosocial assets, and child (age, gender, and temperament) predictors of family functioning, and (c) child adjustment. LPA identified four family functioning profiles: Thriving, Managing, Struggling, and Distressed. Thriving families evinced higher scores on all functioning indicators. Logistic regressions revealed that parents in Thriving families reported significantly lower financial anxiety, less dissatisfaction with partner’s help, less child emotionality, and greater use of cognitive reappraisal, as well as more positive child adjustment in Fall 2020. These findings underscore the multidimensional nature of coping and well-being during COVID-19. Utilizing these levers to promote mental health in families languishing during comparable future crises could promote resilience, thereby protecting children’s well-being.